Fostering effective therapeutic relationships with multicultural and Non-English-speaking adults with physical disabilities - Elnaz Abaei; David Lester (Academia Mental Health & Well-Being)
Counselors, educators, and mental health professionals around the world are increasingly working with clients from diverse cultural backgrounds. Cultural responsiveness in mental health practices is crucial because clients from different cultures may require distinct approaches, coping strategies, and techniques. This includes addressing issues related to illness, disability, racism, and discrimination, all of which necessitate a therapeutic alliance. One particularly vulnerable group is non-English-speaking individuals with congenital or acquired physical disabilities. Enhancing counselors’ cultural awareness and knowledge can significantly improve therapeutic relationships with this population. This article identifies challenges counselors may face when working with non-English-speaking clients with disabilities and offers professional skills and strategies to effectively counsel this population.